THE ART OF GABRIEL SUNDUKYAN'S SATIRE AND THE ROLE OF GIZHMOZI IN THE DRAMA ―THE BROKEN HEART - Melkonyan N., Melkonyan N. (SUSh Scientific Proceedings, 2025)
The aim of this article is to reveal the character of Gizh-Mozi as a unique and multi-layered character in Sundukyan’s work, who acts in the expression of social and human contradictions. The article also emphasizes how Sundukyan presents this character, using the art of satire to criticize falsehood and social structures. To explain why Gizh-Mozi differs from Sundukyan’s other characters and how his actions go beyond social norms. The usage of ―simple‖ and ―harsh‖ languagein the work highlights the falsehood of the society which is vividly expressed in Mozi’s speech. To show that Mozi’s character, on the one hand, unites distorted ―psychologies‖ in society, and on the other hand, becomes an artistic tool to see the reality that not everyone sees. The character of Gizh-Mozi has become an essential part of the satirical art, revealing with their ―humor‖ how social structures define human identity and behavior, obscuring reality. One of the goals of the article is to explain how Sundukyan applied the art of satire in vaudeville, which acts as a powerful tool used by Sundukyan to show the degradation of society. The study of the character of Gizh-Mozi is relevant because it reveals social deception, individual oppression, and the role of societal norms in the formation of personality